Cattleya porphyrascens, a new species (Laeliinae) of the genus Cattleya is described for Minas Gerais State, Brazil - Menezes, Euler Da Luz Fernandes (Phytotaxa, 2023)
A new species of Orchidaceae of the genus Cattleya is described, illustrated, and compared to similar species in morphological and ecological aspects. The new taxon was encountered in the municipality of Diamantina, in the Sempre Vivas National Park, Minas Gerais State (Espinhaço Meridional Complex), Brazil. Cattleya porphyrascens is classified in the Parviflorae series, which comprises more than 50 species. The new species is a saxicolous and cespitose herb evidencing considerable size plasticity (from 6 to 12 cm tall), with flowers varying from 1.5 to 3 cm in diameter. The flowers are almost entirely purple-violet, except for the white fauce of the labellum, which is strongly trilobed, with the middle lobe semi-curved downwards and backwards. It is similar to Cattleya haroldoi and Cattleya vandenbergii, but differs in relevant aspects, as described in the diagnosis.